DIGITAL DEMENTIA: UNRAVELING THE EFFECTS OF THE INTERNET GENERATION ON THE HUMAN BRAIN (REMUNOM, 2024)
Introduction: Dementia is a disease characterized by chronic and progressive neurological symptoms. Similarly, digital dementia causes cognitive decline due to the excessive use of electronic devices, which may anticipate clinical signs and symptoms of other dementia diseases, such as Alzheimer's Disease (AD). Objective: This study aims to conduct an integrative literature review to evaluate the impact of excessive screen use on cognitive impairment, especially in relation to digital dementia. Methodology: This is an integrative literature review, covering studies that investigate the impact of prolonged use of electronic devices on cognitive health. The Health Sciences Descriptors used in English were “Screen Time” and “dementia” and the Boolean logical operator “AND”. A total of 399 articles were identified, of which only 11 met the inclusion criteria: descriptors in the title, time frame and English language. Duplicate studies and those involving animals were excluded. Results: The studies analyzed indicated a significant association between prolonged use of electronic devices and cognitive impairment. The reported symptoms ranged from Mild Cognitive Impairment (MCI) to more severe characteristics, such as memory loss, difficulty concentrating, and increased risk of dementia diseases, such as Alzheimer's Disease (AD). Excessive use of screens for more than 2 hours a day was considered a risk factor, while suggested interventions, such as limiting exposure time, proved effective in reducing these effects. Conclusion: prolonged use of screens can lead to clinical conditions similar to MCI and AD. This requires attention to the formulation of educational and technological policies, aiming to guarantee the cognitive health of future generations.